Self management interventions for breathlessness in adult cancer patients - Howell, Doris M (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The primary objective of this review is to assess the effectiveness of self management educational interventions in reducing breathlessness in adult cancer patients at any disease stage or phase of cancer treatment including post‐treatment survivorship. Secondary objectives are to determine: 1. what specific components of self management interventions (i.e. with or without action plans or problem solving; emphasis on cognitive, behavioral, psychological, educational components) and methods of delivery (i.e. dose or mode) are most effective; and 2. what are the potential modifiers of intervention effectiveness are, such as age, gender, disease stage, disease site and the characteristics of patients who benefit the most.